Photothermal, photocatalytic, and anti-bacterial Ti-Ag-O nanoporous powders for interfacial solar driven water evaporation. Issue 14 (15th July 2021) - Li, Dong; Chen, Shanshan; Huang, Ruirui; Xue, Chaorui; Li, Pengfei; Li, Yangsen; Chang, Qing; Wang, Huiqi; Li, Ning; Jia, Suping; Hu, Shengliang; Yang, Jinlong
Abstract: Interfacial solar driven water evaporation is an attractive and green method to alleviate the scarcity of clean and fresh water, and tremendous efforts have been devoted to prepare efficient photothermal materials. However, the practical condition for interfacial solar driven water evaporation is complex, increasing contamination by pollutants and bacterial can inactive the photothermal materials. Herein, to address this problem, Ti-Ag-O nanoporous powders, which possess photothermal, photocatalytic and anti-bacterial properties, were prepared by TiAg alloy anodization and subsequent laser irradiation method. It was found that metallic Ag nanoparticles, which were mainly formed by TiAg alloy anodization, will be oxidized into Ag2 O nanoparticles after laser irradiation. Through this laser induced transformation, the surface wettability of Ti-Ag-O powders can be improved for the hydrophilicity nature of Ag2 O, and the Ti-Ag-O powders with Ti90Ag10 alloy anodization and subsequent laser irradiation for 10 min showed the highest water evaporation rate (2.27 kg m −2 h −1 ). Meanwhile, this Ti-Ag-O powders also showed the highest photocatalytic property due to the junction between TiO2 and Ag2 O. Moreover, the diffusion inhibition test indicated that antibacterial property of this Ti-Ag-O powders was excellent for the incorporation of Ag/Ag2 O nanoparticles. The as-prepared trifunctional Ti-Ag-O nanoporous powders holds potential for the practical application of interfacial solar driven water evaporation technology, the TiAg alloy anodization and subsequent laser irradiation method could be extended to prepare other multifunctional photothermal materials.